Anti-inflammatory mechanism of Apolipoprotein A-I - Tao, Xia; Tao, Ran; Wang, Kaiyang; Wu, Lidong (Frontiers in Immunology, 2024)
Apolipoprotein A-I(ApoA-I) is a member of blood apolipoproteins,it is the main component of High density lipoprotein(HDL).ApoA-I undergoes a series of complex processes from its generation to its composition as spherical HDL.It not only has a cholesterol reversal transport function, but also has a function in modulating the inflammatory response.ApoA-I exerts its anti-inflammatory effects mainly by regulating the functions of immune cells,such as monocytes/macrophages, dendritic cells, neutrophils, and T lymphocytes. It also modulates the function of vascular endothelial cells and adipocytes. Additionally, ApoA-I directly exerts anti-inflammatory effects against pathogenic microorganisms or their products.Intensive research on ApoA-I will hopefully lead to better diagnosis and treatment of inflammatory diseases.